Prevotella histicola Mitigated Estrogen Deficiency-Induced Depression via Gut Microbiota-Dependent Modulation of Inflammation in Ovariectomized Mice - Huang, Furong; Liu, Xiujie; Xu, Sheng; Hu, Sitao; Wang, Sisi; Shi, Dibang; Wang, Kaicheng; Wang, Zhongxiang; Lin, Qiongqiong; Li, Shan; Zhao, Siyuan; Jin, KeKe; et al. (Frontiers in Nutrition, 2022)
Background: Estrogen deficiency-induced depression is closely associated with an imbalance in intestinal microbiota and inflammation. Prevotella histicola (P. histicola), an emerging probiotic, apparently improves inflammatory responses. This study aims to verify the antidepressant-like effects of P. histicola and clarify its potential mechanisms. Methods: Mice were treated with P. histicola and co-housing after ovariectomy (OVX). The changes in depression-like behaviors among mice were examined by behavioral tasks, and alterations in the microbiota were detected through 16S rRNA sequencing. Changes in neuronal injury, protein synthesis, inflammatory factors, intestinal permeability, and nerve proliferation were observed by H&E, Nissl staining, qRT-PCR, western blotting, and immunofluorescence. Results: P. histicola significantly reduces depression-like behaviors and neuronal damage induced by estrogen deficiency. Additionally, P. histicola significantly increases the abundance of intestinal flora, especially Lactobacillus and Akkermansia. Meanwhile, the co-housed mice also had a better emotional state and neutral structure compared with OVX mice. P. histicola was also found to upregulate tight junction proteins ZO-1, Occludin, Claudin-1, and MUC2 in the ileum and colon, and reduce the levels of inflammatory factors VCAM, MCP-1, IL-6, IL-8, and TNF-α, mainly in the ileum, colon, and decrease the expression of COX-2, TLR4, Myd88, JNK, MCP-1, IL-6, IL-8, TNF-α in the hippocampus. Moreover, significant downregulation of apoptosis (Caspase-3 and Caspase-8) and upregulation of neurotrophic factors (BDNF and Ki-67) were observed after P. histicola treatment. Conclusion: Our data shows that P. histicola significantly mitigates depression of OVX mice through improvement of intestinal microbiota to repair intestinal leakage, and inhibit central inflammation to promote the expression of BDNF for hippocampal neurogenesis. P. histicola may be therapeutically beneficial for PMD.